Structural and Functional Features of Chars From Different Biomasses as Potential Plant Amendments - Marmiroli, Marta; Bonas, Urbana; Imperiale, Davide; Lencioni, Giacomo; Mussi, Francesca; Marmiroli, Nelson; Maestri, Elena (Frontiers in Plant Science, 2018)
Biochars result from the pyrolysis of biomass waste of plant and animal origin. The interest in these materials stems from their potential for soil quality improvement due to increased micro-porosity, carbon pool, water retention, and their active capacity for metals adsorption from soil and irrigation water. Applications in agriculture have been studied under different conditions, but the overall results are still unclear. Char structure, which varies widely according to pyrolysis process and feedstock nature, is thought to be a major factor in the interaction of chars with soil and their metal ion adsorption/chelation properties. Furthermore, biochar nutrients and elemental content can modify soil fertility. Therefore, use of biochars in agricultural settings should be examined carefully by experimental trials. Three key issues in exploitation of biochar are: (i) optimization of pyrolysis for biomass conversion into energy and biochar, (ii) biochar physico-chemical characterization, and (iii) identification of the best possible conditions for its use in soil improvement. Two types of wood pellets, plus digestate and poultry litter, were separately converted into biochar using different technologies: pyrolysis/pyrogasification or catalytic (thermo)reforming. Physico-chemical features for the different biochar batches were measured: pH, conductivity, bulk density, humidity and ash content, particle size, total organic substances, and trace element concentrations. Fine porous structure and total elemental analysis were performed using Environmental Scanning Microscopy (ESEM) coupled with Energy-Dispersive X-ray Spectrometry (EDX). Phytotoxicity tests were performed for each biochar. In conclusion we were able to: i) differentiate the biochars according to their physico-chemical properties, microstructure, elemental contents, and the raw original biomass; ii) correlate the whole biochar features with their respective optimal concentrations when used as plant fertilizers or soil improvers; iii) show that biochars from animal origin were phytotoxic at lower concentrations than those from plant feedstock.